Rethinking the economics of war the intersection of need, creed, and greed - Arnson, Cynthia; Zartman, I. William (Woodrow Wilson Center Press Johns Hopkins University Press, 2005)
This collection of essays questions the adequacy of explaining today's internal armed conflicts purely in terms of economic factors and re-establishes the importance of identity and grievances in creating and sustaining such wars. Countries studied include Lebanon, Angola, Colombia and Afghanistan.